2020
DOI: 10.1021/acs.jpcb.0c08422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PDMS-Based Microfluidics on Belousov–Zhabotinsky Chemical Oscillators

Abstract: Sub-nanoliter volumes of the Belousov−Zhabotinsky (BZ) reaction are sealed in microfluidic devices made from polydimethylsiloxane (PDMS). Bromine, which is a BZ reaction intermediate that participates in the inhibitory pathway of the reaction, is known to permeate into PDMS, and it has been suggested that PDMS and bromine can react (J. Phys. Chem. A. 108, 2004, 1325−1332). We characterize the extent to which PDMS affects BZ oscillations by varying the volume of the PDMS surrounding the BZ reactors. We measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The decay rate is a constant, α = 7 × 10 –3 s –1 , independent of bromine concentration, as expected when the reaction is first-order in bromine concentration. This result is qualitatively consistent with the presence of a reaction between bromine and PDMS determined from modeling the period of the BZ oscillation as a function of PDMS mass …”
Section: Experimental Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The decay rate is a constant, α = 7 × 10 –3 s –1 , independent of bromine concentration, as expected when the reaction is first-order in bromine concentration. This result is qualitatively consistent with the presence of a reaction between bromine and PDMS determined from modeling the period of the BZ oscillation as a function of PDMS mass …”
Section: Experimental Resultsmentioning
confidence: 99%
“…Its main advantages are low cost, optical transparency, and ease of processing, such as high-fidelity molding, toughness, and tensile strength. However, PDMS is permeable to liquids with low dielectric constants, which limits its use in microfluidic applications to aqueous solutions. This material is used to fabricate microfluidic devices holding networks of Belousov–Zhabotinsky (BZ) chemical oscillators, where the oscillators in the aqueous compartments (linear dimensions of 30–100 μm) interact via intermediates that diffuse across the PDMS barriers (wall width of 30–100 μm). In a related system, we showed that collective dynamics are governed by the diffusion of the activator, bromous acid (HBrO 2 ), and bromine (Br 2 ) which participates in the inhibitory pathway. Due to its low dielectric constant, bromine readily permeates PDMS, separating the BZ compartments, leading to a network of inhibitory coupled chemical oscillators.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations